AB0993 Pain relief management of acute osteoporotic vertebral fracture in a real life study. (12th June 2018) - Bertoldo, F.; Gandolini, G.; Venturin, A.; Cisari, C.; Lovato, R.; Longhi, M.; Farina, S.; Bertoldo, E.; Nuti, R.; ,
Abstract : Background: Among all osteoporotic fractures the painful vertebral fractures (PVF) are the minority and their management is challenging for the clinician because the evidences about the best approach are conflicting and of low quality. Moreover there are no guidelines or consensus of experts. A real life picture of the management of the PVF is lacking in the literature. Objectives: The primary end point of the study is to describe the pharmacological and or non-pharmacological management of PVF through the record of use of individual classes, associations and sequences of drugs or procedures. Secondary end point is the outcome of treatment in term of pain, disabilities and quality of life. Methods: We present the iterim analysis results of a multicentric cross-sectional observational study. 400 interviews will be collected consecutively about pain, disability, pharmacological, spinal orthoses and orthopaedic surgery after the diagnosis of PFV in postmenopausal women treated by orthopaedics, endocrinologists, geriatricians, physiatrists, neurosurgeons and E.R. pysicians. Pain and disability were quantified by NRS scale and by QUALEFFO-41. Data collected from the first 100 patients have been analysed. Results: One hundred postmenopausal women aged 73.1±7.49 y.o (age of menopause 48.6±3.9 years, L1-L4 T-score −2.75±0.92, Total hip T-score −2.35±0.98) with a new or first PFV were recorded. About 49% of them had a previous vertebral fracture and 22% a previous non-vertebral fragility fracture, 27% was not on osteoporosis treatment. The interviews were collected 135±114 days from diagnosis of PV, 174±141 days from onset of pain. 92.3%±12% of subjects were treated for pain relief for a mean time of 98±12 days. Only 1.6% of cohort underwent to percutaneous vertebroplasty while 84.6%±17.1% had spinal orthoses. Pharmacological treatment for pain was prescibed to 98.2+7.1% of subjects: acetaminophen (42%), tapentadol (24%), opioids (24%), NSAID (6%) and codeine with acetaminophen (4%). In 95% of patients with spinal orthoses drugs for pain were assumed. In about 40% of cases NSAID was switched to acetaminophen, in 18% opioid and tapentadol switched to NSAID or acetaminophen. Only a few titration of opioids/tapentadol were reported. Not adequate pain relief (NRS scale 6.2±3.1; QUALEFFO-41 pain score 70±14.2) and impairment quality of life (mean total QUALEFFO-41 score 65.1±20.1) were reported. Conclusions: With the limits of the study design and low number of cases, preliminary data seem to confirm an inadequate pain relief in PVF. The emerging critical issues crossing all cathegories of physicians are the lag of diagnosis, the inappropiate use of acetaminophen, the missing tritation of opioids or tapentadol. A definition of optimal management of acute vertebral fracture is missing due to conflicting and scarce evidences in this field predisposing to chronic pain and disability. Disclosure of Interest: None declared